The role of Insulin Resistance in Polycystic Ovarian Syndrome (Latakia University Journal -Medical Sciences Series, 2024)
Polycystic ovarian syndrome (PCOS) is one of the readily recognised endocrine gland illnesses in women, with an incidence range from 2.2% to 26%. Patients experiencing PCOS experience issues involving irregular menstrual periods, hirsutism, acne, being overweigh,. Long-term, low-grade inflammation has emerged as a crucial factor leading to PCOS. A rise in glucose levels may stimulate oxidative stress and a troubling reaction from mononuclear cells (MNC) of females with PCOS, which normally do not rely on fat. The findings of this specific lesson indicated that individuals with the conventional PCOS phenotype had obesity and higher insulin levels and insulin resistance, neglecting the absence of BMI differences from other phenotypes. These data show that insulin resistance is the most significant pathophysiological trait in people with PCOS.